Balto-Slavic and Indo-Iranian - Kortlandt, Frederik (Baltistica, 2016)
The closest relatives of Balto-Slavic are Albanian and Indo-Iranian. Together with Armenian and Thracian, these are the satǝm languages, which together with Greek and Phrygian constitute the eastern part of Classic Indo-European.The obvious common development in this area is the satǝm palatalization, which did not affect Greek and Phrygian. Indo-Iranian was separated from the other satǝm languages by the depalatalization of palatovelars before resonants in the latter.Proto-Indo-European had a threefold distinction between fortis, glottalic lenis, and plain lenis obstruents, all of them voiceless, e.g. *t [t:], *d [ť], *dh [t]. In the Classic Indo-European languages (after their separation from Anatolian and Tocharian), the lenis obstruents became voiced [ʔd], [d], while the fortis remained voiceless [t]. This system was best preserved in Indo-Iranian, Balto-Slavic and Albanian.Another development that seems to be dialectal Indo-European is the retraction of *s to *ṣ after *i, *u, *r, *k in Indo-Iranian, Balto-Slavic, Albanian and Armenian. However, this retraction cannot be dated and may have affected any part of the IndoEuropean dialects. This may also explain the Hittite reflex š of PIE *s.The large majority of special correspondences between Balto-Slavic and IndoIranian are archaisms, not innovations. This is important because it implies that a comparison of Balto-Slavic with Indo-Iranian leads to a reconstruction of an early stage of Indo-European.